Humidity sensor based on electrospun MEH-PPV:PVP microstructured composite - Azmer, M.I.; Zafar, Q.; Ahmad, Z.; Sulaiman, K. (Royal Society of Chemistry, 2016)
The present study demonstrates a solution-processed humidity sensor based on poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene]:polyvinylpyrrolidone (MEH-PPV:PVP) organic microstructured composite thin film. The capacitive type humidity sensor has been fabricated in the surface type geometry of Al/MEH-PPV:PVP/Al, wherein organic composite (MEH-PPV:PVP) has been deposited onto the aluminium electrodes by electrospinning technique. The structural and morphological properties of organic thin film have been characterized by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and atomic force microscopy (AFM). The humidity sensing properties of the sensor have been investigated at ∼1 volt AC operational bias, by measuring the capacitance as a function of a broad range (20-90%) of relative humidity (RH). The temperature and operational frequency dependency of the capacitance of the sensor has also been analyzed in detail. The proposed sensor exhibits high sensitivity (114 fF/% RH @ 100 Hz), small hysteresis (∼2% RH) and fast response (18 s and 8 s for adsorption and desorption processes, respectively). Compared with traditional spin-coated and drop-casted organic humidity sensors, the microstructure composite based sensor has demonstrated significantly improved sensing parameters, highlighting the unique advantages of the electrospinning process for humidity sensor fabrication. The possible humidity sensing mechanism of the proposed capacitive sensor has also been elaborated.